2018
DOI: 10.1090/mcom/3302
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of a class of variational multiscale methods based on subspace decomposition

Abstract: Numerical homogenization tries to approximate the solutions of elliptic partial differential equations with strongly oscillating coefficients by functions from modified finite element spaces. We present a class of such methods that are closely related to the methods that have recently been proposed by Målqvist and Peterseim [Math. Comp. 83, 2014, pp. 2583-2603. Like these methods, the new methods do not make explicit or implicit use of a scale separation. Their comparatively simple analysis is based on the the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 16 publications
0
100
0
Order By: Relevance
“…Quantitative localization results for this particular case have been derived in [1] using classical results from domain decomposition and the convergence theory of iterative solvers, cf. [4,5]. From this theory we know that localization appears if the potential exhibits disorder and satisfies β ε −2 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Quantitative localization results for this particular case have been derived in [1] using classical results from domain decomposition and the convergence theory of iterative solvers, cf. [4,5]. From this theory we know that localization appears if the potential exhibits disorder and satisfies β ε −2 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…see also [21,20] for an alternative constructive proof. Similar to the estimates in Section 3.1, we obtain…”
Section: Localization Of Correctorsmentioning
confidence: 99%
“…In numerical experiments with a Cantor-type geometry, we found the theoretically predicted behavior of (finite element approximationsũ K of) u K . We also observed that the convergence rates of our iterative scheme appear to be robust with respect to increasing K. Theoretical justification and extensions to model reduction in the spirit of [25,28] are subject of current research.…”
Section: Introductionmentioning
confidence: 71%
“…For a numerical illustration, we consider this example in d = 2 space dimensions with c = 1, f ≡ 1, A ≡ 1, and the geometrical parameter C K = 2 K−1 . Note that the ⋅ norm in H (cf (25)(27)…”
mentioning
confidence: 99%